Solano to Share State Building - Vallejo News Chronicle (Vallejo News Chronicle)
The California Maritime Academy in Vallejo is slated to receive a total of $1,420,250 under a proposed five-year building program for state colleges to which the Finance Department has allocated $246,177,250.